Author Correction: Circular RNA CircFndc3b modulates cardiac repair after myocardial infarction via FUS/VEGF-A axis - Venkata Naga Srikanth Garikipati (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.